2004
DOI: 10.2337/diabetes.53.9.2412
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Brain-Derived Neurotrophic Factor in Early Retinal Neuropathy of Streptozotocin-Induced Diabetes in Rats

Abstract: Although neurotrophins have been assessed as candidate therapeutic agents for neural complications of diabetes, their involvement in diabetic retinopathy has not been fully characterized. We found that the protein and mRNA levels of brain-derived neurotrophic factor (BDNF) in streptozotocin-induced diabetic rat retinas were reduced to 49% (P < 0.005) and 74% (P < 0.05), respectively, of those of normal control animals. In addition, dopaminergic amacrine cells appeared to be degenerating in the diabetic rat ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 48 publications
9
149
0
4
Order By: Relevance
“…Long lasting type 1 DM patients may susceptible to microvascular complications; [22][23][24] and macrovascular disease (coronary artery, heart, and peripheral vascular diseases) [25].…”
Section: Clinical Features Of Type I Diabetesmentioning
confidence: 99%
“…Long lasting type 1 DM patients may susceptible to microvascular complications; [22][23][24] and macrovascular disease (coronary artery, heart, and peripheral vascular diseases) [25].…”
Section: Clinical Features Of Type I Diabetesmentioning
confidence: 99%
“…Under normal conditions, it acts as a synaptic modulator in the retinal dopaminergic system (Cellerino et al, 1998). Seki et al (2004) reported that the degeneration of dopaminergic amacrine and RGCs is accompanied by a reduction in BDNF levels in the retina of rats with STZ-induced diabetes and demonstrated the therapeutic potential of BDNF for treating neurodegeneration of dopaminergic amacrine cells in the diabetic retina by intraocular administration. BDNF protects the neurons through (i) TrkB receptors, (ii) insulin-responsive pathways, and (iii) reduction of systemic glucose level locally in the retina.…”
Section: P1115mentioning
confidence: 99%
“…Therefore, the alterations in the dopaminergic system seem to be among the first significant events in the development of DR. Seki et al (2004) named several possible mechanisms underlying the degeneration of dopaminergic amacrine cells in diabetic animals: (i) severe insulin deprivation, (ii) hyperglycemia, and (iii) dysfunction of Müller glial cells. The retina of the insulin-deficient Ins2 Akita mice contained 16% less dopaminergic amacrine cells than nondiabetic age-matched control littermates (Gastinger et al, 2006).…”
Section: P0560mentioning
confidence: 99%
“…[16] Symptoms Blurred vision, polyurea, polyphagia, polydipsia, weight loss, constipation, cramps, thirst, hunger, weakness, [17,18] and candidiasis are common symptoms for both type-1 and type-2 DM. [1] Apart from that the patients with Type-1 DM have both microvascular problems [5][6][7][8][9][10] and macrovascular diseases such as heart, peripheral vascular and coronary artery diseases [11,12] while patients with Type 2 DM have high risk of large vessel atherosclerosis commonly associated with obesity, hypertension, hyperlipidaemia. [11,12,19,20] Most patients are die with type-2 diabetes due to cardiovascular complications and end stage renal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of insulin leads to chronic hyperglycemia with disturbances of fat, protein and carbohydrate metabolism. [1][2][3][4] Long term diabetes cause tissue or vascular damage and leads some dangerous complications like neuropathy [5,6] , nephropathy [7,8] , retinopathy [9,10] , cardiovascular complications [11,12] and ulceration. [13,14] First diabetic classification and diagnostic criteria was given by World Health…”
Section: Introductionmentioning
confidence: 99%